(untitled) (Revista de Ciências Agroveterinárias, 2020)
The use of tools such as forest modeling becomes increasingly important in forest planning as they generate accurate estimates of the stands’ production. The aim of this study was to adjust the hypsometric, volumetric, and taper models for four Pinus species in the Mountain region of Santa Catarina in Brazil. The species Pinus taeda, Pinus elliottii, Pinus greggii, and Pinus patula were all planted and maintained under the same forest management plan. The 14-year-old stand is located in the municipality of Correia Pinto, Santa Catarina, Brazil. For the analyses, mathematical models were adjusted based on data from the forest census. The following statistical criteria were used to choose the most appropriate model: the adjusted coefficient of determination (R² adj), standard error (Sy.x%) and graphic residual analysis. The hypsometric equations presented relatively low values for the adjusted R², ranging from 0.14 to 0.35 for the species, while the values for Sy.x% ranged between 7.67% and 4.86%. As for the volumetric equations, the adjusted R² was above 0.91, and Sy.x% was under 10%. With regard to the taper functions, the Hradetzky model most appropriately described the stem profile of the species, with values above 0.96 for the adjusted R² and under 10% for Sy.x%. The Naslund, Spurr I and II, and modified Naslund models were selected to estimate the species’ volumetry. The Hradetzky taper model was found to be superior to the others and was thus selected to determine the stem profile of the species in the field research area.